The formation of cyanoborate liquid clathrates with water or cresol as promoters - Davis, Bridgit Helen (Department of Chemistry, 2016)
If host and guest components form a liquid clathrate only when a third component is present, the third component is a promoter of liquid clathrate formation. The importance of promoters was verified by promoting liquid clathrate formation in guest-host combinations which do not form liquid clathrates without a promoter. The validity of the conventional definition of liquid clathrates was probed with respect to the absence of host in the excess guest layer and with respect to the fixed maximum guest to host ratio. A model which allows for the effect of promoters on liquid clathrates was proposed. The II electron rich nature of the guest is important in the model, so the guests, furan, thiophene and benzene, were used to probe the dependence of cyanoborate liquid clathrate formation on the IT electron rich nature of the guest. Differences in the electronic nature of the promoters, water and cresol, caused differences in the ease of promoting cyanoborate liquid clathrate formation, in the stability and composition of the liquid clathrates formed, and in the interactions between the promoter and the components of the liquid clathrate (host anion, host cation and guest). In promoting liquid clathrate formation, the promoter separated the host cation-anion pairs so that the guest interacted favourably with the host cation. The guest to host ratio was dependent on the amount of promoter present in the liquid clathrate, and favourable interactions of the promoter with liquid clathrate components caused the liquid clathrate to expand as it accommodated increased amounts of promoter and guest. Favourable interaction of the promoter with the components of the liquid clathrate compensated for the energy required to separate the host cation-anion pairs.